KEARIFAN LOKAL DALAM LEGENDA KEAGAMAAN MASYARAKAT BANJAR - Sri Wahyu Nengsih (Universitas Lambung Mangkurat, 2020)
Local Wisdom In The Banjar Community Religious Legends. The purpose of this study is to reveal the local wisdom of the Banjar people in the religious legend of the Banjar community. This research was conducted using a semiotic approach with a descriptive type of research. This research data in the form of words, sentences, and expressions in the religious legend of the Banjar community. The data source of this research is the book